2017
DOI: 10.1038/srep40680
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of a novel human adenovirus type 8 strain causing a prolonged, multi-state keratoconjunctivitis epidemic in Germany

Abstract: The German infectious disease surveillance system revealed an increase of epidemic keratoconjunctivitis (EKC) from an average of 320 cases/year (2001 to 2010) up to 2146 and 1986 cases in 2012 and 2013, respectively. From November 2011 until December 2013 (epidemic period) 85% of typed isolates were human adenovirus type 8 (HAdV-D8), whereas only low level circulation (19%) of HAdV-D8 was observed outside the epidemic period. In order to investigate whether a novel monophyletic HAdV-D8 strain prevailed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…25 Our finding is also consistent with other studies that showed HAdV8 to be a major culprit of adenovirus-associated conjunctivitis. 9,26,27 In addition, the predominance of HAdV species C genotypes, particularly HAdV1 and HAdV2, found among young children is also supported by other studies. 28 As young children have developing immune system, they may be more prone to infections.…”
Section: Dovepresssupporting
confidence: 78%
“…25 Our finding is also consistent with other studies that showed HAdV8 to be a major culprit of adenovirus-associated conjunctivitis. 9,26,27 In addition, the predominance of HAdV species C genotypes, particularly HAdV1 and HAdV2, found among young children is also supported by other studies. 28 As young children have developing immune system, they may be more prone to infections.…”
Section: Dovepresssupporting
confidence: 78%
“…The HAdV‐8 strains were also the major cause of many conjunctivitis outbreaks in different populations around the world such as in Tunisia, 39 China, 40 South Korea, 41 Brazil, 42 India, 39 and Germany 34 . Detailed sequence comparisons among HAdV‐8 in Vietnam (VN2017) with 60 other HAdV‐8 genomes isolated from various parts of the world (Figure 3) revealed that the genome of VN2017 had high nucleotide sequence homology with HAdV‐8 genomes in the International cluster including HAdV‐8 from Japan (99.80%), Saudi Arabia (99.80%), Germany (99.78%), and United States (99.79%).…”
Section: Discussionmentioning
confidence: 99%
“…HAdV‐D8 is the most frequently reported type among confirmed cases of EKC . It was first isolated in the United States in 1955, during an outbreak of conjunctivitis in a shipyard .…”
Section: Introductionmentioning
confidence: 99%
“…13 HAdV-D8 is the most frequently reported type among confirmed cases of EKC. [14][15][16] It was first isolated in the United States in 1955, during an outbreak of conjunctivitis in a shipyard. 17 The isolated strain was designated as the prototype and named Trim (AB448767).…”
mentioning
confidence: 99%